Primitivism, science, and the Irish revival - Garrigan Mattar, Sinéad (Oxford University Press, 2004)
Covering the works of W.B. Yeats, J.M. Synge and Lady Gregory this text explores the primitivism of the Irish Revival in relation to comparative science.
10.1093/acprof:oso/9780199268955.001.0001
Keywords: English literature; Primitivism in literature; Literature and anthropology; Literature and science; Primitivism; Civilization; Celtic; in literature; Mythology; Celtic; in literature; Celts in literature